Evaluation of spin in abstracts of papers in psychiatry and psychology journals. Issue 5 (5th August 2019) - Jellison, Samuel; Roberts, Will; Bowers, Aaron; Combs, Tyler; Beaman, Jason; Wayant, Cole; Vassar, Matt
Abstract : We have identified 'spin' in abstracts of randomised controlled trials (RCTs) with nonsignificant primary endpoints in psychiatry and psychology journals. This is a cross-sectional review of clinical trials with nonsignificant primary endpoints published in psychiatry and psychology journals from January 2012 to December 2017. The main outcome was the frequency and manifestation of spin in the abstracts. We define spin as the 'use of specific reporting strategies, from whatever motive, to highlight that the experimental treatment is beneficial, despite a statistically nonsignificant difference for the primary outcome, or to distract the reader from statistically nonsignificant results'. We have also assessed the relationship between industry funding and spin. Of the 486 RCTs examined, 116 were included in our analysis of spin. Spin was identified in 56% (n=65) of those included. Spin was found in 2 (2%) titles, 24 (21%) abstract results sections and 57 (49.1%) abstract conclusion sections. Evidence of spin was simultaneously identified in both results and conclusions sections in 15% of RCTs (n=17). Twelve articles reported industry funding (10%). Industry funding was not associated with increased odds of spin in the abstract (unadjusted OR: 1.0; 95% CI: 0.3 to 3.2). We found no relationship between industry funding and spin in abstracts. These findings raise concerns about the effects spin may have on clinicians. Further steps could be taken to address spin, including inviting reviewers to comment on the presence of spin and updating Consolidated Standards of Reporting Trials guidelines to contain language discouraging spin.